Cancer risk in patients with diabetic nephropathy: A retrospective cohort study in Hong Kong. Issue 38 (September 2017) - Cheung, Chi Yuen; Ma, Maggie Kam Man; Chak, Wai Leung; Tang, Sydney Chi Wai
Abstract : Abstract: Diabetic nephropathy (DN) is a leading cause of end-stage kidney disease nowadays. Certain cancers are more common in patients with diabetes mellitus. However, there are no data concerning the cancer pattern in patients with DN. The aim of this study is to investigate the site-specific cancer risk and mortality in these patients. A retrospective cohort study of 5643 DN patients between 2000 and 2015 was conducted in 2 large hospitals in Hong Kong. Incidence and mortality of various cancers were compared with those of general population using standardized incidence ratios (SIRs) and standardized mortality ratios (SMRs) respectively. With 24, 726 person-years follow-up, 250 cancers were diagnosed. Overall cancer incidence was similar between DN patients and the general population (SIR 1.05, 95% confidence interval [CI] 0.92–1.19). However, certain site-specific cancers are increased in DN patients: the highest risk was observed for laryngeal cancer (SIR 3.03, 95% CI 1.11–6.60), followed by cancers of liver (SIR 1.96, 95% CI 1.35–2.76) and colorectum (SIR 1.92, 95% CI 1.53–2.37), but the risk of prostate cancer was lower (SIR 0.48, 95% CI 0.21–0.95) in the males with DN. The SMR of all cancers was 1.17 (95% CI 1.01–1.37). For individual specific site, only colorectal cancer carried a significant higher mortality risk (SMR 2.45, 95% CI 1.82–3.23). Our data suggested that DN is associated with increased incidence of cancers of colorectum, liver, and larynx but decreased incidence of prostate cancer. Moreover, there is increased mortality of colorectal cancer in patients with DN.